Zingiber officinale volatile oil: clinical trial on Brugia Malayi infection in Kalimantan area - Mulyaningsih Mulyaningsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: According to the fact, there is chance that the Zingiber officinale volatile oil can be developed for treatment elephantiasis in man. However, up to now there was no study yet on the efficacy of the phytopharmaca against filaria.Objective: The clinical trial was designed to know the effect and the safety of application of Zingiber officinale volatile oil as anti-filariasis agent in the treatment of Brugia malayi infection in Kalimantan area.Methods: In this study, 40 patients suffered from filariasis malayi were divided into 2 groups. Zingiber officinale volatile oil in honey syrup was given to each patient of group I. Honey syrup as plasebo was given to each patient of group II. The treatment was given for 28 consecutive days each. The density of microfilariae before and after treatment of each group were recorded and assessed using Pre-test and Post-test by using probit analysis.Results: This study showed' that the average value of microfilaria density before and after treatment count per 60 ul blood in placebo group were 64.9 ± 96.4 and 90.4 ± 122.0. While in volatile oil's group were, 92.1 ± 118.3 and 56.6 ± 77.0 respectively. MfD50 of placebo group before and after treatment is 27.75, and 44.99. MfDso of volatile oil's group before and after treatment is 44.42, and 37.06.Conclusion: Zingiber officinale volatile oil can be developed for treatment elephantiasis in man.Key words : microfilaria density - phytopharmaca - volatile oil - filariasis malayi - elephantiasis.